STUDY OF THE DISTRIBUTION OF PERMANENT FIRST MOLAR TEETH ERUPTION IN CHILDREN WITH STUNTING - Fitriani, Desi; Dwi, Rosada Sintya; Tarasati, Tiara (Cahaya Ilmu Bangsa Institute, 2025)
Seberang Ulu I District was one of the districts with a high level of stunting status in Palembang. This study aims to determine the distribution pattern of permanent first molar eruption in stunted children, by looking at the distribution of permanent first molar eruption in stunted children based on age, gender, and stunting status in the working area of ​​1 Ulu Health Center. The research method used was analytical observational research with a sample size of 33 people. The results showed that the frequency distribution based on gender, girls experienced a faster rate of tooth eruption than boys, the number of children with short stunting was greater than the number of children with very short stunting. It was known that 15 respondents who had experienced molar tooth eruption, the most were in the short stunting category with 13 people. The 18 respondents who had not experienced molar tooth eruption, the most were in the short stunting category with 13 people